Exploring emotion work from the narratives of fathers of children with a neurodisability - Bogossian, Aline (Intervention, 2021)
Although parenting a child with a neurodisability (i.e., autism, cerebral palsy, or epilepsy) can be a life-altering experience, fathers have been generally underrepresented in research on parenting and their unique experiences underexplored. The aim of this study was to explore feelings, emotions and their management through a secondary analysis of data from an Interpretive Phenomenological Analysis study involving eleven Canadian fathers. The two main themes were as follows: a dance of emotions in the father-child connection and spaces for emotional expression and support. Drawing on Hochschild’s theory of emotion work and theories of masculinity, the complexity and contradictions of this parenting experience are revealed. We suggest that attending to the emotional work of fathers may help social workers connect with and support them.